Systematic review and meta-analysis of antibiotic strategies for survival in patients with drug-resistant Acinetobacter baumannii infection: does quantity matter? - De Rorna, Masrahma Reinataya; Ramadhani, Alfiyah; Hibatulloh, Muhammad Farhan; Agustina, Dini (Faculty of Medicine, Universitas Trisakti, 2025)
Background Acinetobacter baumannii is an opportunistic pathogen frequently associated with severe hospital-acquired infections, particularly in intensive care units, and is characterized by high levels of antibiotic resistance, including to carbapenems. The rising prevalence of multidrug- and pan-drug-resistant strains poses significant therapeutic challenges and underscores the need for optimized treatment strategies to improve survival outcomes. This systematic review and meta-analysis evaluates the impact of different antibiotic treatment modalities (monotherapy versus combination) on the clinical outcome of patients with Acinetobacter baumannii infection. Methods This systematic review and meta-analysis followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. To find pertinent studies released up to 3 January 2025 a thorough search was done in electronic databases such as PubMed, Embase, ScienceDirect, Cochrane, EBSCOhost, Google Scholar, and Scopus. Results This systematic review and meta-analysis identified 20 studies for inclusion. No statistically significant overall survival difference was found (Pooled OR = 0.83, 95% CI [0.66- 1.03], p = 0.09), but subgroup analyses indicated that combination therapy markedly enhanced survival rates in patients with carbapenem-resistant Acinetobacter baumannii (CRAB) infection, APACHE II scores below 20, and bloodstream infections. Meta-regression suggested that age may adversely affect treatment efficacy. A trend favoring combination therapy was consistent across subgroups, despite some results not reaching statistical significance. Conclusion This systematic review and meta-analysis highlights the treatment challenges of drug-resistant Acinetobacter baumannii, particularly MDRAB, XDRAB, and CRAB strains. Combination therapy offers potential benefits in CRAB and moderate-severity cases but is not universally superior to monotherapy. Treatment outcomes are influenced by patient-specific factors such as age, infection type, and disease severity.